On the Simultaneous Determination of Current Expenditure, Real Capital, Fee Income, and Public Debt in Norwegian Local Government - Audun Langørgen (Statistics Norway, Research Department, 1995)
An extended community preference model including real and financial investments is estimated on accounting time-series data for the local public sector in Norway. The estimation results indicate considerable sluggishness in local public spending, both in current expenditure and investment spending. A positive shift in grants or taxes will in the short run lead to reductions in the net debt, due to the sluggish spending adjustment. But as spending adjustments take place, the effect on the net debt is reversed, so the long run effect is positive. The long run elasticities of factor demand and net debt with respect to exogeneous income constraints do not differ significantly from unity. The estimated price elasticities suggest that factor demand is close to neutral-elastic in the long run. Higher factor prices involve higher production costs, and local authorities are thus induced to increase user charges.
Keywords: C32; H72; H74; 330; Local government; local public finance; public expenditure; investment; public debt.